2003
DOI: 10.1034/j.1600-0676.2003.01742.x
|View full text |Cite
|
Sign up to set email alerts
|

Previous hepatitis B virus infection is associated with worse disease stage and occult hepatitis B virus infection has low prevalence and pathogenicity in hepatitis C virus‐positive patients

Abstract: Our findings suggest that previous HBV infection among anti-HCV patients is associated with worse disease stage. In these patients, the prevalence of occult HBV infection is low and there is no difference in distribution among patients with or without markers of previous HBV infection. Furthermore, it does not seem to be associated with disease stage. Lastly, at least among patients with chronic hepatitis, it does not seem to affect the severity of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 37 publications
8
30
1
2
Order By: Relevance
“…The prevalence of occult infection seems to be closely related to the prevalence of HBV infection in different parts of the world. Several investigators have shown an intermediate to high occurrence of HBV occult infection, both in serum and in liver tissue (1,2,4,(8)(9)(10)(11)(12)(13)(14)(15). In Brazil, particularly in the Southeast region, the prevalence of HBV infection is very low (21) and this may have contributed to our results of an HBV occult infection rate close to zero.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…The prevalence of occult infection seems to be closely related to the prevalence of HBV infection in different parts of the world. Several investigators have shown an intermediate to high occurrence of HBV occult infection, both in serum and in liver tissue (1,2,4,(8)(9)(10)(11)(12)(13)(14)(15). In Brazil, particularly in the Southeast region, the prevalence of HBV infection is very low (21) and this may have contributed to our results of an HBV occult infection rate close to zero.…”
Section: Discussionmentioning
confidence: 40%
“…infections by HBV such as low HBV DNA and HBsAg levels (2), mutations in HBV DNA sequence (3), viral DNA integration in the host genome (4), infection of peripheral blood mononuclear cells (5), production of immune complexes containing HBV (6), altered host immune response (7), and interference of other viruses (mainly hepatitis C virus, HCV) (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HBV DNA has been found in serum by PCR in 6.7% to 52% (13,15,16) of HBsAg-negative patients with chronic HCV infection, in 5% to 76% (7,10,30) of patients with chronic liver disease of no defi ned etiology, and in 0% (15) to 15% (21) of healthy donors.…”
Section: Discussionmentioning
confidence: 95%
“…Despite evidence that co-infection may accelerate the progress to liver disease (9,41) , be related to the emergence of HCC (34,37,38) , and adversely infl uence the response to HCV treatment (7,9,13,41) , other studies show that occult infection does not interfere with the natural history of the disorder in this population (12,15,16,22) .…”
Section: Introductionmentioning
confidence: 99%
“…Nosso achado vai contra a teoria da manutenção residual do vírus B neste cenário, sugerindo desta forma a ausência de seus epítopos em hepatócitos, ao menos em quantidades suficientemente capazes de induzir uma maior resposta citotóxica e fibrogênica, ou mesmo pautando a hipótese da supressão não citolítica de sua suposta replicação viral, exercido por células T através da liberação de citoquinas capazes de suprimir a transcrição de seu genoma sem causar dano celular 22 . Embora não realizada neste estudo, a diferenciação entre o padrão anti-HBcAg isolado e o perfil sorológico completo (anti-HBcAg[+] e anti-HBsAg[+]) para a avaliação da influência da infecção pregressa pelo VHB na hepatopatia do vírus C foi proposta por alguns autores, partindo do pressuposto de que a primeira situação estaria associada a um maior dano hepático 6,23 . Contudo, neste ponto a literatura tem demonstrado resultados conflitantes.…”
Section: Discussionunclassified